PENGEMBANGAN MEDIA ARTICULATE STORYLINE UNTUK MENINGKATKAN MINAT BELAJAR SISWA PADA MUATAN PELAJARAN IPA KELAS V SD - Alfiza Kharisma Putri; Alvia Andini; Nabila Putri Astuti; Arita Marini (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2023)
Articulate Storyline is software that is used as a medium for communication and e-learning tools that function to present information with a specific purpose in order to produce interactive learning. The purpose of this research is to develop Articulate Storyline media in science subjects with the aim of increasing student learning interest in grade V elementary school. The method used in this research is research and development (R&D). And the methods used to collect data are observation, interview and questionnaire. The results of this study, Articulate Storyline learning media is feasible to use because it facilitates and helps teachers in delivering learning materials and makes it easier for students to understand learning materials and can attract students' attention and interest and students can learn interactive independently. The conclusion of this study is that the use of articulate storyline-based learning media can increase student interest in science subject content and improve learning outcomes.